2023
DOI: 10.3390/buildings13010237
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Study on Built-Up Cold-Formed Steel Beams with Web Openings Connected by Spot Welding

Abstract: This paper presents a numerical parametric study on cold-formed steel built-up beams subjected to bending. The cold-formed steel built-up elements are efficient structural elements that are easy to assemble during the construction process, ensuring material savings and potential for standardization, thus making them more suitable for mass production. A new technological solution for built-up steel beams with webs made of corrugated steel sheets and flanges made of cold-formed steel profiles, assembled through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…The past research focused on Cold-Formed Steel (CFS) members has initiated the development of CFS built-up beams effectively with respect to transverse load, rotation, web crippling and web buckling capacity and compared the structural behaviour with conventional built-up sections (Dar et al, 2019; Lalthazuala and Singh, 2019; Meza et al, 2020; Serror et al, 2016; Ye et al, 2016; Zhou and Shi, 2011). Cristian and Ungureanu (2023) carried out a parametric study on spot welded built-up CFS beams with web openings and identified that the weakest portion is the thickness of corrugated web. The role of outstand and extended types of stiffener on the flexural capacity of CFS built-up beams is also explored (Muftah et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The past research focused on Cold-Formed Steel (CFS) members has initiated the development of CFS built-up beams effectively with respect to transverse load, rotation, web crippling and web buckling capacity and compared the structural behaviour with conventional built-up sections (Dar et al, 2019; Lalthazuala and Singh, 2019; Meza et al, 2020; Serror et al, 2016; Ye et al, 2016; Zhou and Shi, 2011). Cristian and Ungureanu (2023) carried out a parametric study on spot welded built-up CFS beams with web openings and identified that the weakest portion is the thickness of corrugated web. The role of outstand and extended types of stiffener on the flexural capacity of CFS built-up beams is also explored (Muftah et al, 2019).…”
Section: Introductionmentioning
confidence: 99%